NUTRIENT CYCLING IN EUCALYPTUS DUNNII: MICRONUTRIENTS IN THE LITTERFALL - Momolli, Dione Richer; Schumacher, Mauro Valdir; Ludvichak, Aline Aparecida; dos Santos, Kristiana Fiorentin; de Souza, Huan Pablo; Guimarães, Claudiney do Couto (Floresta, 2019)
The evaluation of litterfall and nutrient return is important for understanding the dynamics of nutrient cycling. Although required in smaller quantities by plants, micronutrients have unique importance in biogeochemical regulation. The objective of the present study was to quantify the litterfall and the concentration of micronutrients in the different fractions and seasons of the year in Eucalyptus dunnii stand. Four plots of 20 m x 21 m were demarcated. The collection of leaf litter, twigs (diameter <0.5 cm) and miscellaneous resulted in the installation of 4 collectors with an area of 0.5 m² in each plot. For the quantification of the thick branches fraction (diameter> 0.5 cm), four useful areas of medium-diameter trees were demarcated in each plot. The leaf fraction represented 59% of litterfall and the transfer order was Mn> Fe> B> Zn> Cu, totaling 8.04 kg ha-1. The leaf fraction presented the highest concentrations for B and Mn. The litterfall was seasonal with summer and spring differing statistically from winter and the temperature variable explains the deposition pattern of the same.